Enzymatic Production of Ecodiesel by Using a Commercial Lipase CALB, Immobilized by Physical Adsorption on Mesoporous Organosilica Materials - Carlos Luna; Victoria Gascón-Pérez; Francisco J. López-Tenllado; Felipa M. Bautista; Cristóbal Verdugo-Escamilla; Laura Aguado-Deblas; Juan Calero; Antonio A. Romero; Diego Luna; Rafael Estévez (Catalysts, 2021)
The synthesis of two biocatalysts based on a commercial Candida antarctica lipase B, CALB enzyme (E), physically immobilized on two silica supports, was carried out. The first support was a periodic mesoporous organosilica (PMO) and the second one was a commercial silica modified with octyl groups (octyl-MS3030). The maximum enzyme load was 122 mg enzyme/g support on PMO and 288 mg enzyme/g support on octyl-MS3030. In addition, the biocatalytic efficiency was corroborated by two reaction tests based on the hydrolysis of p-nitrophenylacetate (p-NPA) and tributyrin (TB). The transesterification of sunflower oil with ethanol was carried out over the biocatalysts synthesized at the following reaction conditions: 6 mL sunflower oil, 1.75 mL EtOH, 30 °C, 25 μL NaOH 10 N and 300 rpm, attaining conversion values over 80% after 3 h of reaction time. According to the results obtained, we can confirm that these biocatalytic systems are viable candidates to develop, optimize and improve a new methodology to achieve the integration of glycerol in different monoacylglycerol molecules together with fatty acid ethyl esters (FAEE) molecules to obtain Ecodiesel.